ANTIOXIDANT ACTIVITY TEST OF ANDROGRAPHOLIDE IN BITTER HERBS USING DPPH SCAVENGING - Ni Made Pitri Susanti; Ni Kadek Warditian; I Made Agus Gelgel Wirasuta (Journal of Health Sciences and Medicine, 2017)
Abstract Bitter herbs (Sambiloto) have many pharmacological activities including antioxidant, antidiabetic, anticancer, antihyperlipidemic and anti-inflammation. Andrographolide is a diterpene compounds contained in bitter herbs. It is known that andrographolide compound responsible for the pharmacological activity of the bitter herbs. This study investigated DPPH free radical scavenging activity from andrographolide diterpene lactone. This study was initiated with the isolation of andrographolide compound from bitter herbs and then testing their DPPH free radical scavenging. The results suggested that andrographolide had IC50 value of 5.45 mg. This means andrographolide has 50% DPPH inhibition effect, i.e 5.45 mg.